ANALYSIS OF THE EFFECT OF WEATHER CONDITIONS AND CONVERSATIONS ON DRIVER SITUATION AWARENESS USING THE SITUATION AWARENESS RATING TECHNIQUE (SART) METHOD - Romadoni, Muhammad Ilham; Suryadi, Akmal (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2024)
Driving is an activity of controlling vehicles on the road, either using motorcycles or cars that can pose a risk of accidents, the factors that cause accidents include human factors, vehicle factors, and environmental factors. The purpose of this study was to determine the effect of weather conditions and conversation on the situation awareness of car drivers (driving simulator) using the Situation Awareness Rating Technique (SART) method. The research subjects are Industrial Engineering students of UPN "Veteran" East Java, while the research object is situation awareness during sunny and rainy weather conditions, with and without being invited to a conversation. The statistical test used is the paired sample t-test. there is no difference in the average SA value or no significant effect on sunny weather conditions without being invited to a conversation and with being invited to a conversation which shows a sig. (2-tailed) of 0.578 0.05. Whereas in rainy weather conditions without being invited to have a conversation and with being invited to have a conversation there is a difference in the average SA value or there is a significant effect on the driver where the sig value. (2-tailed) of 0.024 0.05.